The relationship between lower extremity alignment and Medial Tibial Stress Syndrome among non-professional athletes - Raissi Golam; Cherati Afsaneh; Mansoori Kourosh D; Razi Mohammad D (BMC, 2009)
Abstract Objective To determine the relationship between lower extremity alignment and MTSS amongst non-professional athletes Design In a prospective Study, sixty six subjects were evaluated. Bilateral navicular drop test, Q angle, Achilles angle, tibial angle, intermalleolar and intercondylar distance were measured. In addition, runner's height, body mass, history of previous running injury, running experience was recorded. Runners were followed for 17 weeks to determine occurrence of MTSS. Results The overall injury rate for MTSS was 19.7%. The MTSS injury rate in girls (22%) was not significantly different from the rate in boys (14.3%). Most MTSS injuries were induced after 60 hours of exercise, which did not differ between boys and girls. There was a significant difference in right and left navicular drop (ND) in athletes with MTSS. MTSS had no significant correlation with other variables including Quadriceps, Tibia and Achilles angles, intercondylar and intermaleolar lengths and lower extremity lengths. Limitation All measurements performed in this study were uniplanar and static. The small sample size deemed our main limitation. The accurate assessment of participants with previous history of anterior leg pain for MTSS was another limitation. Conclusion Although a significant relationship between navicular drop and MTSS was found in this study; there was not any significant relationship between lower extremity alignment and MTSS in our sample study.